Multiwavelength study of the intriguing massive star CPD--59 2629 (Tr 16-22) - Combi, Jorge Ariel (2011)
We report preliminary results of a multi-wavelength (radio-optical-X-ray) study of the massive star CPD -59 2629 (Tr 16-22) in the Carina Nebula (NGC 3372). This star has historically shown a large X-ray excess (log L_{X}/L_{bol} < -6 or even larger), which is one order of magnitude larger than expected from single massive O-type stars. A colliding wind scenario is a plausible explanation. On this subject, we searched for non-thermal radio emission and used high-resolution optical spectroscopy to check for multiplicity and investigate the nature of the stars as well as the origin and excess of the X-ray emission. We detected long-term radial-velocity and X-ray variability. Both results suggest that Tr 16-22 is a long-term massive binary system and a variable colliding wind shock scenario.